A young female presenting with heart failure secondary to eosinophilic myocarditis: a case report and review of the literature - Ralapanawa, Dissanayake Mudiyanselage Priyantha Udaya Kumara (BMC Res Notes, 2018)
BACKGROUND: Eosinophilic myocarditis is one of the fatal complications of idiopathic hypereosinophilic syndromes. Given the rarity of this form of myocarditis, it is often under-recognized. We describe a young girl who presented with features of heart failure. To our knowledge, this is the first reported case of eosinophilic myocarditis in a young Sri Lankan female. CASE PRESENTATION: A previously healthy 21 year old Sri Lankan female admitted with shortness of breath for 1 week duration with associated low grade fever and profuse sweating. She was mildly febrile and dyspnoeic with absent ankle oedema. She was tachycardic and had elevated Jugular venous pressure with negative Kussmaul sign. Blood pressure was 100/70 mmHg. Clinically there was no cardiomegaly and heart sounds were slightly muffled with gallop rhythm. Bilateral basal fine end inspiratory crackles and mild hepatosplenomegaly were noted. The laboratory examinations showed leucocytosis with severe eosinophilia with no abnormal cells. Her ESR, Troponin I and Brain natriuretic peptide were elevated with normal CRP and electrocardiogram showed sinus tachycardia with wide spread ST depression. Heart failure was evident on chest X-ray and 2D-echocardiogram showed global left ventricular hypokinesia with 40% ejection fraction and a thin layer of pericardial effusion. Mild hepatosplenomegaly without lymphadenopathy was detected in the ultrasound scan. Bone marrow biopsy showed hypereosinophilia with no evidence of bone marrow infiltration. FIP1L1–PDGFRA fusion transcript and BCR–ABL transcript were not detected. Secondary causes for hypereosinophilia were excluded and the diagnosis of idiopathic hypereosinophilic syndrome and eosinophilic myocarditis was made. She had good response to steroids clinically and biochemically with complete recovery of left ventricular function. She is now on steroid to be continued at least 6 months to 1 year. CONCLUSION: Eosinophilic myocarditis is a rare but fatal disease if left untreated. Hence clinicians should have high index of suspicion to diagnose eosinophilic myocarditis in clinical context of heart failure due to myocarditis. The diagnoses of eosinophilic myocarditis may often be challenged especially in a poor recourse setting. However available investigation should be used to diagnose this condition without delay. Early treatment with systemic steroids may prevent fatal outcome and therapies for this disease have yet to be validated in large prospective studies.